(untitled) - Hew, Denis (Singapore, 2007)
Against the backdrop of significant developments in regional economic cooperation and integration over the past decade, this book presents some of the key challenges facing ASEAN as it embarks on a bold and ambitious project to establish an ASEAN Economic Community by 2015. Organized under the auspices of the ASEAN-Australia Development Cooperation Programs Regional Economic Policy Support Facility (AADCP-REPSF), the book brings together authoritative studies written by prominent experts and academics on issues pertaining to ASEAN economic integration.
Keywords: Tổ chức ASEAN,Đông Nam Á,Đông Nam Á,ASEAN,Southeast Asia,Southeast Asia; Hòa nhập kinh tế,Chính sách kinh tế,Commercial policy,Economic integration